The epidemiology and outcomes of invasive Candida infections among organ transplant recipients in the United States: results of the Transplant‐Associated Infection Surveillance Network (TRANSNET). Issue 6 (14th November 2016) - Andes, David R.; Safdar, Nasia; Baddley, John W.; Alexander, Barbara; Brumble, Lisa; Freifeld, Allison; Hadley, Susan; Herwaldt, Loreen; Kauffman, Carol; Lyon, G. Marshall; Morrison, Vicki; Patterson, Thomas; et al.
Abstract: Background: Invasive candidiasis (IC) is a common cause of mortality in solid organ transplant recipients (OTRs), but knowledge of epidemiology in this population is limited. Method: The present analysis describes data from 15 US centers that prospectively identified IC from nearly 17 000 OTRs. Analyses were undertaken to determine predictors of infection and mortality. Results: A total of 639 cases of IC were identified. The most common species was Candida albicans (46.3%), followed by Candida glabrata (24.4%) and Candida parapsilosis (8.1%). In 68 cases >1 species was identified. The most common infection site was bloodstream (44%), followed by intra‐abdominal (14%). The most frequently affected allograft groups were liver (41.1%) and kidney (35.3%). All‐cause mortality at 90 days was 26.5% for all species and was highest for Candida tropicalis (44%) and C. parapsilosis (35.2%). Non‐white race and female gender were more commonly associated with non‐ albicans species. A high rate of breakthrough IC was seen in patients receiving antifungal prophylaxis (39%). Factors associated with mortality include organ dysfunction, lung transplant, and treatment with a polyene antifungal. The only modifiable factor identified was choice of antifungal drug class based upon infecting Candida species. Conclusion: These data highlight the common and distinct features of IC in OTRs.